Superlasional Kemampuan Berpikir Kreatif dan Keterampilan Menulis Puisi Mahasiswa Melalui Metode Konstruktivisme dan Pemodelan - Efrianto Efrianto (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to describe the superlative comparison of creative thinking ability and poetry writing skills among students using constructivism and modeling methods. The research adopts a qualitative approach with a descriptive method. The research sample consists of two out of four classes, selected through purposive sampling technique. Data collection involves a set of performance tests or instruments for each variable under investigation. The data analysis technique employed in this quantitative research utilizes statistics. Two types of statistics are utilized for data analysis, namely descriptive statistics and inferential statistics. The research findings indicate two main points. Firstly, the learning of poetry writing skills using the constructivism instructional model yields better results compared to the modeling instructional model. Secondly, the use of constructivism instructional model for poetry writing skills among students with high creative thinking ability has a more significant impact compared to the use of modeling instructional model. Therefore, it can be concluded that students who engage in learning with the constructivism instructional model, particularly those with high creative thinking ability, exhibit improved poetry writing skills.